Stomach Content Analysis of Anabas testudineus from the Lubuk SiamLake Siak Hulu Sub-district Kampar District Riau Privince - Dalan Trenget Manik; Ridwan Manda Putra; Windarti Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Anabas testudineus  commonly inhabits the Lubuk Siam Lake. information on the feeding habit of that fish, however, is rare.  To understand the type of food consumed by that fish, a research has been conducted in July to August 2019. Sampling was conducted once/ two weeks interval for two months. There were 97 fishes captured, but 22 of them had empty stomach and they can not be used for stomach content analysis. Theanalysis was conducted using avolumetric method.Stomach content wasanalyzed as a basis to calculate the Preponderance Index (PI).Results shown thatthe main food of the fish  was plant (PI 56.96%), thecomplementary food was fish and unidentified debris (PI was 26.56% and  12.50% respectively), and additional food was insects and crustacean  ((PI was 3.13% and 0.85% respectively). Data obtained indicate that this fish can be categorized as omnivore.Keywords: Climbing perch, Gut Content Analysis, Volumetric method,Oxbow Lake